THE RELATIONSHIP BETWEEN ACCOUNTING INFORMATION SYSTEMS INPUT AND DISCLOSURE IN THE FINANCIAL STATEMENTS OF IRAQI PRIVATE BANKS (World Economics and Finance Bulletin, 2025)
This research deals with the relationship between the inputs of accounting systems and financial disclosure is one of the main factors that enhance confidence among investors the data entered into the accounting systems. The study aimed to analyze the relationship the accuracy, integrity